Caffeine consumption and risk of dyskinesia in CALM‐PD. Issue 3 (21st January 2013) - Wills, Anne‐Marie A.; Eberly, Shirley; Tennis, Marsha; Lang, Anthony E.; Messing, Susan; Togasaki, Daniel; Tanner, Caroline M.; Kamp, Cornelia; Chen, Jiang‐Fan; Oakes, David; McDermott, Michael P.; Schwarzschild, Michael A.; et al.
ABSTRACT Background Adenosine A2A receptor antagonists reduce or prevent the development of dyskinesia in animal models of levodopa‐induced dyskinesia. Methods We examined the association between self‐reported intake of the A2A receptor antagonist caffeine and time to dyskinesia in the Comparison of the Agonist Pramipexole with Levodopa on Motor Complications of Parkinson's Disease (CALM‐PD) and CALM Cohort extension studies, using a Cox proportional hazards model adjusting for age, baseline Parkinson's severity, site, and initial treatment with pramipexole or levodopa. Results For subjects who consumed >12 ounces of coffee/day, the adjusted hazard ratio for the development of dyskinesia was 0.61 (95% CI, 0.37–1.01) compared with subjects who consumed <4 ounces/day. For subjects who consumed between 4 and 12 ounces/day, the adjusted hazard ratio was 0.73 (95% CI, 0.46–1.15; test for trend, P = .05). Conclusions These results support the possibility that caffeine may reduce the likelihood of developing dyskinesia. © 2013 Movement Disorder Society